The Mage's Images: Heinrich Khunrath in His Oratory and Laboratory, Volume 2 : Prologue: Bio-Bibliography and Introduction to Khunrath's Images - Forshaw, Peter, (Aries Book Series ;, 2024)
This is the 1st volume in a 4-volume work entitled The Mage's Images . The work provides the first in-depth examination of the life and works of Heinrich Khunrath (1560-1605), 'one of the great Hermetic philosophers', whose Amphitheatre of Etern